2019
DOI: 10.1136/gpsych-2018-100001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of excessive internet use and its correlation with associated psychopathology in 11th and 12th grade students

Abstract: BackgroundGlobally, the number of internet users has crossed the three-billion mark, while in India users grew over 17% in the first 6 months of 2015 to 354 million. This study presented a background on internet use and the existence of excessive internet use.AimTo study the extent of internet use in 11th and 12 grade students and the psychopathology, if any, associated with excessive internet use.Methods426 students who met the inclusion criteria were recruited from 11th and 12th grade classes from Kendriya V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
5
17
1
2
Order By: Relevance
“…According to study by Kumar et al, excessive internet users were more in commerce and humanities as compared to science and majority of science students were normal users. 9 Present study has got results contrary to this study which might be due to different sample size and region of study. Asiri et al, in their study points out that males are more efficient at using internet, receive lesser supervision by parents and end up using internet more for entertainment needs in comparison to females which increases their potential risk for internet addiction.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…According to study by Kumar et al, excessive internet users were more in commerce and humanities as compared to science and majority of science students were normal users. 9 Present study has got results contrary to this study which might be due to different sample size and region of study. Asiri et al, in their study points out that males are more efficient at using internet, receive lesser supervision by parents and end up using internet more for entertainment needs in comparison to females which increases their potential risk for internet addiction.…”
Section: Discussioncontrasting
confidence: 80%
“…Globally, the number of internet users has crossed the three-billion mark, while in India users grew over 17% in the first 6 months of 2015 to 354 million. 9 An article published way back in The Guardian in March 2008 said "Addiction to internet 'is an illness' and evidence shows that heavy users suffer isolation, fatigue and withdrawal symptoms. 10 12 Jain et al observed the prevalence of internet addiction was 93.3%.…”
Section: Discussionmentioning
confidence: 99%
“…A community-based study reported a relationship between pathological internet use and SDQ total difficulty score and conduct problems (Ozturk, Ekinci, Ozturk, & Canan, 2013). In another study, 11 th and 12 th -grade students reported that excessive internet use had both positive (prosocial) and negative impacts (peer problems, conduct problems, emotional problems, and hyperactivity) on the SDQ (Kumar et al, 2019). Adolescents with PIU had significantly higher scores on SDQ in comparison to controls on conduct problems, hyperactivity, emotional symptoms, and total difficulty domains and lower scores on the prosocial behaviors domain (Cao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] Kumar et al reported the prevalence of internet addiction among 11 th /12 th students as mild in 23.9%, moderate in 30.3% and severe in 1.4%. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%